(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
Recently, due to the numerous benefits of e-government implementation, so it becomes inevitable for both developed and developing countries. However, the benefits of implementing e-government, it faces many challenges in developing countries. In this regard many studies were conducted on a number of developing countries in order to determine the challenges to e-government implementation. This article conducted to review the most important studies in this regard and focus on the most common challenges to e-government implementation in developing countries. From the related literature it clears that the most common challenges to e-government in developing countries are represented in five categories; technical challenges, organizational challenges, social issues, financial challenges and human challenges, such category include a number of factors. All these challenges have a direct or indirect effect on each other. So governments in developing countries have to focus on these five categories and seeking for treat them